Modified discrete LQ control algorithm for situations with the scan-period variance - Cvejn, Jan (Springer, 2016)
Computer-based control applications, especially if they run under general- purpose operating systems, often exhibit variance of the scan period of processing inputs and outputs. Although this fact is usually not taken into account when discrete control algorithms are used, it can cause worse performance of the control loop in comparison to a theoretical case. In this paper we describe a modified discrete LQ control algorithm that takes disturbances of the scan period into account and partially compensates their impact. We also show that such a controller can be implemented even on low-performance hardware platforms, if they are equipped with a sufficient amount of memory
Modifikovaný diskrétní LQ říidcí algoritmus pro případy s proměnnou vzorkovací periodou
Keywords: Optimal control; LQ controller; Linear systems; Discrete control; optimální řízení; LQ regulátor; lineární systémy; diskrétní řízení